2018
DOI: 10.1016/j.ebiom.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Lighting a Fire in the Tumor Microenvironment Using Oncolytic Immunotherapy

Abstract: Oncolytic virus (OV) therapy is potentially a game-changing cancer treatment that has garnered significant interest due to its versatility and multi-modal approaches towards tumor eradication. In the field of cancer immunotherapy, the immunological phenotype of the tumor microenvironment (TME) is an important determinant of disease prognosis and therapeutic success. There is accumulating data that OVs are capable of dramatically altering the TME immune landscape, leading to improved antitumor activity alone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 72 publications
(84 reference statements)
0
98
0
6
Order By: Relevance
“…Necrosis can induce an inflammatory response that can further improve the antitumor effect. 21 Therefore, compared with DDP, oHSV2 not only kills tumors directly but also can further stimulate the antitumor immune response to enhance the tumoricidal ability. magnification, Â200).…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis can induce an inflammatory response that can further improve the antitumor effect. 21 Therefore, compared with DDP, oHSV2 not only kills tumors directly but also can further stimulate the antitumor immune response to enhance the tumoricidal ability. magnification, Â200).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly larger scale future studies using catheterized urine need to be conducted to accurately evaluate the potentially important role of the bladder microbiome in both bladder cancer pathogenesis/progression and response to immunotherapy agents. ONCOLYTIC VIRUS THERAPY: CONVERTING "IMMUNOLOGICALLY COLD" TUMORS INTO INFLAMED "HOT" TUMORS One intervention capable of dramatically altering the TME immune landscape, is the use of oncolytic or "cancer-killing" viruses (OVs) (32). OVs lead to improved anti-tumor immunity through the induction of both innate and adaptive immune responses, releasing the full range of tumor-associated antigens (TAAs) into an inflammatory environment via tumor lysis and the induction of immunogenic cell death, disrupting the immunosuppressive TME (33)(34)(35)(36).…”
Section: The Urinary Microbiome: a Potential Emerging Factor In The Imentioning
confidence: 99%
“…Previous studies have shown that OVs can infect and replicate in CAFs (123) and ECs (124), resulting in their elimination and subsequently increasing immune infiltration in the TME. Most preclinical studies have concluded that OVs have the potential to convert immunologically inert tumors into highly immune-reactive ones and have the ability to attack tumor malignancies in multiple different ways by targeting different subsets of TME cells and disrupting the tumor landscape (125). Indeed, OVs create an acute localized inflammatory response in the tumor that favors immune cell recruitment and activation and results in a therapeutic antitumor effect.…”
Section: Ov-mediated Immunotherapymentioning
confidence: 99%